"It's because We are 'Loose Girls' That's why We had Children with MINUSTAH Soldiers": A Qualitative Analysis of Stigma Experienced by Peacekeeper-Fathered Children and Their Mothers in Haiti. Issue 23 (December 2022) - Vahedi, Luissa; Stuart, Heather; Etienne, Stéphanie; Wisner, Sandra; Lee, Sabine; Bartels, Susan Andrea
Sexual abuse and exploitation (SEA) perpetrated by UN peacekeepers while on mission is a violation of human rights and undermines the goal of upholding human rights in countries that host peacekeeping missions. In addition to survivors, children fathered by peacekeepers are also victims of SEA that need protection. Stigma poses negative life course consequences for SEA survivors and their peacekeeper-fathered children. However, there is a considerable lack of empirical research concerning the stigma experiences of SEA survivors and their children in post-colonial contexts. The present study addresses this knowledge gap by drawing on The United Nations Stabilization Mission in Haiti as a case study to examine the lived experiences of stigma among SEA survivors and their resultant children. Using 18 qualitative semi-structured interviews conducted in 2017 with Haitian women raising peacekeeper-fathered children, we organized qualitative codes according to Link and Phelan's conceptual model of stigma. The stigmatization process was explored through the themes of labeling, stereotyping, separation, and status loss and discrimination, as described by Link and Phelan. In addition, we nuanced the lived experiences of stigma by discussing the buffering roles of familial acceptance, skin phenotype, and the Haitian context. The findings have implications for the UN. We advocate that stigma be recognized and acted upon as a fundamental protection concern for SEA survivors and their children. Accordingly, the UN has an obligation to provide stigma-related supports for victims and complainants as well as to facilitate long-term child support for the children left behind by peacekeepers.